(untitled) (Research, Society and Development, 2022)
Introduction: Intraoral peripheral giant cell granuloma is considered a reactional lesion. Although its etiology is not clearly established, trauma and local irritants are associated with its occurrence. It commonly presents as a nodular lesion, which may present with superficial ulceration. The most frequent intraoral location is in the mandible, between the fifth and sixth decades of life. The lesion does not have specific imaging criteria for diagnosis. Histologically, it is composed of mononuclear cells and multinucleated giant cells in a stroma of fibrous connective tissue with different degrees of inflammation. Objective and case report: The article aims to present a case report of a patient with peripheral giant cell lesion in the large mandible. Surgical treatment for excision of the lesion was performed in a hospital environment, under the effect of general anesthesia. Final considerations: The control of local irritating agents and the complete excision of the lesion, associated with an adjuvant therapy, such as peripheral osteotomy, guarantee an effective treatment, reducing the possibility of recurrence.